The pragmatic functions of emojis in Arabic tweets - Alharbi, Amjad; Mahzari, Mohammad (Frontiers in Psychology, 2023)
Emojis have been used on different platforms and in different languages to express feelings and emotions in online communication, which has led to their widespread familiarity among social media users worldwide. The current study is concerned with the pragmatic functions (speaker and contextual meanings) of emojis in Arabic tweets. The study used mixed methods to analyze the use of emojis and emoji position to identify their functions and possible gender similarities and differences. The dataset of this study consists of 421 Arabic tweets by Arab users at the beginning of 2022 (149 by male users and 272 by females). This study addressed three questions: (1) What are the common emojis used in Arabic tweets and their position in the tweet? (2) What are the pragmatic functions of these emojis? (3) What are the possible differences and similarities between male and female users in the use of emojis? The findings revealed that Loudly Crying Face (😭), Red Heart (❤️), Face with Tears of Joy (😂), Broken Heart (💔), Smiling Face with Heart-Eyes (😍), Pleading Face (🥺), Slightly Smiling Face (🙂), Pensive Face (😔), and Weary Face (😩) were preponderant in Arabic tweets. Also, this study found seven pragmatic functions ranging from the most to the least frequent: Multiple functions, Reaction, Action, Decoration, Physical action, Softening, and Tone modification. Regarding the role of gender, there were both similarities and differences in terms of the frequency of emoji use, emoji position, and function. Moreover, the findings showed the importance of context to interpreting the functions of emojis. Finally, the findings have implications for emoji designers and Natural Language Processing (NLP).